The influence of match status on attacking patterns of play in elite soccer teams - Machado, DJ. C.; Barreira, D.; Garganta, J. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2014)
The attacking performance in elite soccer is a complex process that is influenced by several situational variables, such as match status. The objective of this study was to investigate the influence of match status on the configuration of attacking patterns of play performed by elite soccer teams based on the analysis of matches played by the semi-finalists of the 2010 FIFA World Cup. We observed 28 matches, 7 per semi-finalist team of the 2010 FIFA World Cup, resulting in 1938 attacks, further ordered according to match status (winning, drawing or losing). The SoccerEye observational instrument, SoccerEye recording software (version 3.2), and SDIS-GSEQ analysis software (version 5.1) were used. The national teams of Germany, Netherlands and Uruguay showed more difficulty in scoring goals while losing the match, although they scored after a positive crossing or after a free kick committed by the opposing team. The national team of Spain tended to shoot into the opponent goal after short passing, in both losing and winning situations. We conclude that attacking patterns of play were influenced by match status in the 2010 FIFA World Cup, with the exception of Spanish national team, which tended to use an indirect style of play with no dependence on match status.